2019
DOI: 10.1002/cplu.201800539
|View full text |Cite
|
Sign up to set email alerts
|

Assembling All‐Solid‐State Lithium–Sulfur Batteries with Li3N‐Protected Anodes

Abstract: The construction of all‐solid‐state batteries is now easier after the successful synthesis of sulfur‐based solid electrolytes with extremely high ionic conductivities. Utilizing lithium metal as the anode in these batteries requires a protective solid electrolyte layer to prevent corrosion due to the highly reactive nature of lithium. Li3N coating on lithium metal is a promising way of preventing the degradation of the electrolyte during charge and discharge. In this study, utilization of a Li3N‐coated lithium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 17 publications
0
18
0
Order By: Relevance
“…This mapping also shows that the sides and bottom of the isle are rich in C, F, and some N. This distribution could be the result of LiTFSI decomposition and the probable formation of a At first, Li 3 N crystal precipitates could form, which are not soluble and do not dissolve with further cycling, thus forming the isles. Kızılaslan et al 23 used Li 3 N as a protective layer on a lithium anode to enhance the cycling of the battery. After that, further decomposition of the salt may result in the formation of Li 2 S, LiC x F y , LiF, Li x CNF 3 , and Li y SO x surrounding the isle.…”
Section: Resultsmentioning
confidence: 99%
“…This mapping also shows that the sides and bottom of the isle are rich in C, F, and some N. This distribution could be the result of LiTFSI decomposition and the probable formation of a At first, Li 3 N crystal precipitates could form, which are not soluble and do not dissolve with further cycling, thus forming the isles. Kızılaslan et al 23 used Li 3 N as a protective layer on a lithium anode to enhance the cycling of the battery. After that, further decomposition of the salt may result in the formation of Li 2 S, LiC x F y , LiF, Li x CNF 3 , and Li y SO x surrounding the isle.…”
Section: Resultsmentioning
confidence: 99%
“…Synthesis of solid electrolyte used in this study was reported in the previous study. [ 10 ] Phase analysis of MoS 2 coating was carried out by Rigaku D/MAX 2000 type X‐ray spectrometer with Cu K α radiation between 5° and 90° with 1° min −1 scan rate. The morphology and elemental mapping of the MoS 2 coating were observed with an FESEM (FEI Quanta FEG 450).…”
Section: Methodsmentioning
confidence: 99%
“…Li 3 N coating was shown to increase capacity retention in our previous study. [ 10 ] However, the small grain sizes (<160 nm), and weak interconnection is not capable of suppressing Li metal dendrites for long cycles. [ 11 ] Moreover, the voltage stability window of Li 3 N is only ≈0.45 V and unstable to reduction (≤2.4 V vs Li/Li + ) which is low for practical applications.…”
Section: Introductionmentioning
confidence: 99%
“…The electrolyte solution was prepared by lithium bis(trifluoromethanesulfonyl)imide (10.0 g), and LiNO 3 (0.24 g) in solution of 1,3‐dioxolane (17 ml) and 1,2‐dimethoxyethane (17 ml). Button cells (CR2032‐type) were assembled with as‐synthesized polypropylene films, anode, cathode and electrolyte in glovebox under Ar atmosphere …”
Section: Methodsmentioning
confidence: 99%
“…Button cells (CR2032-type) were assembled with as-synthesized polypropylene films, anode, cathode and electrolyte in glovebox under Ar atmosphere. [40] The electrochemical workstation (CHI 660B) was employed to measure the electrochemical impedance spectrometry (EIS) of cells with a perturbation of 5 mV between 0.1 Hz to 100 kHz. The galvanostatic charge-discharge test was performed between 1.8 and 3.0 V by using a battery test system (LAND CT2001A).…”
Section: Electrochemical Measurementsmentioning
confidence: 99%